Strategi Penggunaan Metode Jigsaw dalam Meningkatkan Pemahaman Materi Pendidikan Kewarganegaraan di MI Negeri 3 Pringsewu - Kemala , Rizqa Arini; Julia, Rispa; Wahyuni, Rita (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the effectiveness of the Jigsaw method in improving students' understanding of Civic Education material at MI Negeri 3 Pringsewu. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection. The research subjects were fifth-grade students, with data collected through observation, tests, and interviews. The results indicate that the implementation of the Jigsaw method significantly enhances students' understanding, as reflected in the improvement of average scores across cycles. Additionally, this method fosters student engagement in group discussions and a sense of responsibility in learning. Thus, the Jigsaw method can be an effective alternative in Civic Education learning to enhance students' comprehension and social skills.